Alexithymia Correlates with Social Media Addiction in Students of Junior High School 1 Sumbang Banyumas - Wintana, Dwi Amalia Putri Bian; Apriliyani, Ita; Maryoto, Madyo (Journal Keperawatan, 2025)
Background: Alexithymia is a psychological condition characterized by difficulty in identifying, understanding, and expressing emotions. Individuals with alexithymia often experience difficulties in managing emotions effectively, so this condition is often associated with various psychological problems (anxiety, depression, to addictive behavior). The prevalence of alexithymia is quite high in various populations including adolescents and this shows the importance of a deep understanding of the factors and impacts that contribute to the emergence of this condition. The current phenomenon of adolescents who are always associated with antisocial life and are more focused on social media to other virtual worlds may be the impact of alexithymia. Purpose: To test the relationship between alexithymia and social media addiction in students of SMPN 1 Sumbang Banyumas.. Methods: This study is a quantitative study with a correlation analytical approach. The population taken were patients who would undergo surgery with subarachnoid block anesthesia using a saturated sampling technique with a sample size of 76 respondents. The research instrument used a physical status observation sheet according to ASA standards and an observation sheet for achieving a Bromage score ≤ 2 and a watch to calculate the achievement time. Results: Based on statistical analysis, it shows a very significant positive relationship between alexithymia scores and social media addiction scores with a p-value of 0.000 and a correlation coefficient value of 0.631. Conclusion: There is a relationship between alexithymia and social media addiction in students at SMPN Sumbang Banyumas (the relationship between the two variables is strong). This can happen because the higher the level of alexithymia of a student, the higher the level of social media addiction.